Spectators’ perceptions regarding the security measures taken in soccer stadiums - Ali Eraslan (ROL Spor Bilimleri Dergisi)
The aim of this study was to examine the spectators’ perceptions regarding the security measures taken in soccer stadiums. The unrelated question model, which is one of the quantitative methods, was used in the research. The research group consists of 474 soccer spectators selected. The data were obtained from the spectators of professional soccer clubs in the first league in the 2021-2022 season in Ankara, Turkey. This study was designed as a general survey research, one of the quantitative research methods. According to the data obtained from the research, perceptions of security measures in stadiums differ according to gender, age, education level and how the spectators define themselves as a spectator. As a result, it is seen that the highest score belongs to the "perception that violence can be prevented by the security forces" sub-dimension, and the lowest score belongs to the "perception of controls at entrance to stadium" sub-dimension according to the spectators' perceptions of stadium security. Especially, women spectators find the security measures in the stadiums sufficient, but they think that the security forces cannot manage it in any violent event that may occur. In addition, it is seen that the participants with a high level of education and who define themselves as “very good spectators” have higher perceptions of the security measures in the stadiums.